2015
DOI: 10.1097/hjh.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP and the risk of incident hypertension

Abstract: See original paper on page 966 I n many different areas of cardiovascular physiology [1], cardiac biomarkers have been shown to be very useful tools in evaluating cardiac (dys)function [2], assessing diagnosis [3,4], guiding subsequent management [5], stratifying prognosis [6], as well as assessing total cardiovascular risk [7]. Moreover, they significantly contribute to our knowledge of mechanisms of disease genesis and progression. In this area, the release of natriuretic peptides has been extensively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“… 11 Studies have found that NT-pro BNP has important significance in cerebrovascular diseases. 12 , 13 In this study, the level of NT-pro BNP of the observation group was significantly higher than that of the control group, which was consistent with the results of the current studies. BNP can promote natriuresis, inhibit secretion of antidiuretic hormone and sympathetic nerve impulse, and regulate baroreceptor.…”
Section: Discussionsupporting
confidence: 91%
“… 11 Studies have found that NT-pro BNP has important significance in cerebrovascular diseases. 12 , 13 In this study, the level of NT-pro BNP of the observation group was significantly higher than that of the control group, which was consistent with the results of the current studies. BNP can promote natriuresis, inhibit secretion of antidiuretic hormone and sympathetic nerve impulse, and regulate baroreceptor.…”
Section: Discussionsupporting
confidence: 91%
“…Аргументация полученных данных может быть обеспечена тем, что в почках BNP увеличивает СКФ, расслабляя мезангиальные клетки, и ингибирует фракционную реабсорбцию натрия в канальцах, тем самым усиливая натрийурез и снижая АД, а также уменьшает сосудистое сопротивление, расслабляя гладкомышечные клетки артерий. Поэтому многие исследователи отмечают, что более низкие "исходные" концентрации BNP и NT-proBNP у пациентов с ГБ были связаны с более высоким риском развития как ХСН, так и поражения органов-мишеней [10,11]. Тем не менее, не вызывает сомнения и тот факт, что в патогенезе поражения органов-мишеней большую роль играют и другие системы: ренин-ангиотензин-альдостероновая система (РААС) и симпато-адреналовая система (СНС).…”
Section: материал и методыunclassified